2016
DOI: 10.1111/bph.13466
|View full text |Cite
|
Sign up to set email alerts
|

Berberine improves mesenteric artery insulin sensitivity through up‐regulating insulin receptor‐mediated signalling in diabetic rats

Abstract: *Feng-Hao Geng and Guo-Hua Li contributed equally to this work. BACKGROUND AND PURPOSEBerberine, a small molecule derived from Coptidis rhizome, has been found to be potent at lowering blood glucose and regulating lipid metabolism. Recent clinical studies have shown that berberine reduces blood pressure and increases systemic insulin sensitivity in patients with metabolic syndrome; however, the underlying mechanism is still unclear. Here, we investigated the mechanism by which berberine improves vascular insul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(28 citation statements)
references
References 60 publications
1
25
1
1
Order By: Relevance
“…Furthermore, pro-and antiinflammatory mediators released from perivascular adipose tissue are involved in the development of atherosclerosis [181], suggesting that adipocytes may play a key role in diabetes-associated cardiovascular dysfunctions. The results demonstrated that berberine could protect cardiovascular functions by reducing the risk of hypertension [123,126] and coagulation [134], attenuating cardiac hypertrophy [115,129,132] and cardiac arrhythmias [110,113], and inhibiting potential cardiovascular damages associated with dyslipidemia [74,114,116,[119][120][121]124,125,130,135,136]. In addition, berberine reduced obesity and cardiovascular risk at least in part via modulating adipocyte populations and inflammatory state in the adipose tissues [112,117,118,128,131].…”
Section: Vascular Protectionmentioning
confidence: 96%
See 1 more Smart Citation
“…Furthermore, pro-and antiinflammatory mediators released from perivascular adipose tissue are involved in the development of atherosclerosis [181], suggesting that adipocytes may play a key role in diabetes-associated cardiovascular dysfunctions. The results demonstrated that berberine could protect cardiovascular functions by reducing the risk of hypertension [123,126] and coagulation [134], attenuating cardiac hypertrophy [115,129,132] and cardiac arrhythmias [110,113], and inhibiting potential cardiovascular damages associated with dyslipidemia [74,114,116,[119][120][121]124,125,130,135,136]. In addition, berberine reduced obesity and cardiovascular risk at least in part via modulating adipocyte populations and inflammatory state in the adipose tissues [112,117,118,128,131].…”
Section: Vascular Protectionmentioning
confidence: 96%
“…Berberine has also been shown to reduce total cholesterol and LDL-C in clinical trials [23,60]. In studies in vitro, berberine alleviated palmitate-induced endothelial dysfunction via upregulation of endothelial nitric oxide synthase (eNOS) and downregulation of nicotinamide adenine dinucleotide phosphate oxidase 4 (NOX4) [114], an enzyme involved in age-associated cardiovascular dysfunction via oxidative stress and inflammation [150]; it also inhibited HG-potentiated platelet aggregation [134], suppressed HGinduced endothelial dysfunction and restored NO generation possibly via suppressing ectopic miR-133a expression and restoring peroxisome proliferator-activated receptor (PPAR) γ and AMPK signaling [44,121,123,125,126]. In another study, it reduced oxidized LDL-induced inflammatory responses in macrophages via AMPK activation and nuclear factor (NF)-B inhibition [135].…”
Section: Vascular Dysfunctionmentioning
confidence: 99%
“…Metformin (MET) has been used as the first-line drug therapy for T2DM, due to its excellent inhibitory effect on hepatic glucose production. [10][11][12] Berberine (BB) is an isoquinoline alkaloid originally isolated from Chinese herb Coptis chinensis (Huang lian), which exerts anti-diabetic [13][14][15][16] and anti-inflammatory activities. [17][18][19] Over the past decades, a number of experimental and clinical studies have been centralized on the biological activities of Metformin, Berberin and their derivatives.…”
mentioning
confidence: 99%
“…The animals were housed in plastic cages, corncob bedding and maintained in a temperature‐ and humidity‐controlled room (24 ± 2°C and 60% humidity) with 12 h light–dark cycles. Diabetes was induced by feeding a high‐fat diet (HFD) and administration of a low‐dose of streptozotocin (STZ, 27.5 mg·kg −1 ) to the SUR1 −/− rats; this method has been in use for several years (Reed et al ., ; Ti et al ., ; Geng et al ., ). Rats were fed a standard irradiated HFD (34.5% fat, 17.5% protein and 48% carbohydrate; Beijing Keaoxieli FEEDS Co., Ltd, China) for 4 weeks.…”
Section: Methodsmentioning
confidence: 97%